Pengaruh Kebebasan Dalam Bekerja, Keberhasilan Diri Dan Toleransi Akan Resiko Terhadap Minat Mahasiswa Menjadi Wirausaha Di Surabaya Barat - Arika Winda Cahya Suritno (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2020)
The purpose of this observation is to find out and analyze the influence of the factors of freedom at work, self-success and risk tolerance towards students' interest in becoming entrepreneurs in West Surabaya. Types of data use quantitative data and data sources use primary data. To collect research data is to distribute a questionnaire of 100 respondents. With the sampling technique method non-probability (Non probability sampling methods). Processing and data analysis using SPSS application support. Validity test, reliability test and multiple linear regression analysis are the data analysis techniques used. From the results of research validity test of all variables declared valid, because of significance 0.6. The f test shows that all independent variables, freedom in works, self-success and tolerance for risks have significant on the interest of student to become entrepreneurs. Whereas the t-test results showed that the variables of freedom of work, self-success and tolerance for risk have a positive and significant effect on on the interests of students to become entrepreneurs.